Napisz wyrazenie nie używając nawiasów i zredykuj wyrazy podobne :

-2(2a-3b+5)+(4a-7b+3)-(-3a-2b-1)
(4a+2b-7)-(a-3b-4)-(2a-b-3)
-(-2a+5b-4)+(2a-3b-4)-(-3a-b+2)
(-5a+b-3)-(2a-3b+5)-(4a-b-8)
2x-7-[5x*-3x-(2-4x+2x*]
3-x*-[2-2x*-(3x*-2x+1)]
3x*-5x-[1-3x-(2+4x-x*)

* znaczy do potęgi drugiej. ; ))

3

Odpowiedzi

Najlepsza Odpowiedź!
2010-02-16T15:42:16+01:00
-4a+6b-10+4a-7b+3+3a+2b+1= 3a+b-6
4a+2b-7-a+3b+4-2a+b+3=a+6b
2a-5b+4+2a-3b-4+3a+b-2= 7a-7b-2
-5a+b-3-2a+3b-5-4a+b+8=-11a+5b-4
1 5 1
2010-02-16T15:42:54+01:00
-2(2a-3b+5)+(4a-7b+3)-(-3a-2b-1)= -4a+6b-10+4a-7b+3+3a+2b+1= 3a+b-6

(4a+2b-7)-(a-3b-4)-(2a-b-3)= 4a+2b-7-a+3b+4-2a+b+3= a+6b

-(-2a+5b-4)+(2a-3b-4)-(-3a-b+2)= 2a-5b+4+2a-3b-4+3a+b-2= 7a-7b-2

(-5a+b-3)-(2a-3b+5)-(4a-b-8)= -5a+b-3-2a+3b-5-4a+b+8= -11a+5b

2x-7-[5x²-3x-(2-4x+2x²)]= 2x-7-(5x²-3x-2+4x-2x²)= 2x-7-5x²+3x+2-4x+2x²= -3x²+x-5

3-x²-[2-2x²-(3x²-2x+1)]= 3-x²-(2-2x²-3x²+2x-1)= 3-x²-2+2x²+3x²-2x+1= 4x²-2x+2

3x²-5x-[1-3x-(2+4x-x²)]= 3x²-5x-(1-3x-2-4x+x²)= 3x²-5x-1+3x+2+4x-x²= 2x²+2x+1
2010-02-16T15:50:34+01:00
-2(2a-3b+5)+(4a-7b+3)-(-3a-2b-1)
-4a+6b-10+4a-7b+3+3a+2b+1=3a+b-6

(4a+2b-7)-(a-3b-4)-(2a-b-3)
4a+2b-7-a+3b+4-2a+b+3=a+6b

-(-2a+5b-4)+(2a-3b-4)-(-3a-b+2)
2a-5b+4+2a-3b-4+3a+b-2=7a-7b-2

(-5a+b-3)-(2a-3b+5)-(4a-b-8)
-5a+b-3-2a+3b-5-4a+b+8=-11a+5b

2x-7-[5x*-3x-(2-4x+2x*]
2x-7-(5x²-3x-2+4x-2x²)=2x-7-5x²+3x+2-4x+2x²=-3x²+x-5

3-x*-[2-2x*-(3x*-2x+1)]
2-x²-(2-2x²-3x²+2x-1)=-2-x²-2+2x²+3x²-2x+1=4x²-2x-3

3x*-5x-[1-3x-(2+4x-x*)
3x²-5x-(1-3x-2-4x+x²)=3x²-5x-1+3x+2+4x-x²=2x²+2x+1